Inverted Nasal Papilloma: Retrospective Analysis of our Clinical Results - Sedat Aydın; Hacer Baran; Mehmet Gökhan Demir; Serdar Ceylan; Elif Uysal (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]To evaluate our cases diagnosed with inverted nasal papilloma (INP) and to contribute to the literature on the future surgical and clinical approaches in the light of the results obtained.[¤]METHODS[|]In this study, 80 patients who underwent surgical treatment between 2010–2018 in our clinic were evaluated retrospectively. The patients were analysed according to demographic data, complaints, primary region, clinical stage, computed tomography (CT) scores, surgical methods, malign transformation and recurrence.[¤]RESULTS[|]Of the patients, 65 (81.25%) were male, and 15 (18.75%) were female. The mean age was 53+-12 years. The most common complaint was unilateral nasal obstruction (96.2%). The most common primary site of INP was the lateral nasal wall (52.5%). Bone erosion was observed in 11 patients (13.7%). Of the 74 (92.5%) patients who underwent endoscopic sinus surgery (ESS), 23 (28.8%) of them underwent lateral rhinotomy to complete the tumor excision. 9 (11.3%) patients underwent revision surgery due to recurrence. In 4 (5%) of the cases, nonkeratinized squamous cell carcinoma was observed.[¤]DISCUSSION AND CONCLUSION[|]INPs have been investigated for both their diagnosis and treatment earlier with the introduction of endoscopy into the routine nasal examination. We think that close follow-up of cases is very important, especially because of the high rate of recurrence of these tumors and the transformation to malignancy.[¤]